Analisis Makna Denotatif Dan Konotatif Pada Tekslaporan Hasil Observasi Karangan Siswa Kelas VII Mts Negeri Surakarta II - Arif, Muhammad Zaenuddin; , Drs. Andi Haris Prabawa, M.Hum (2016)
This study aimed to describe the form meaningful words denotative and connotative text observation report results bouquet seventh grade students of MTs Negeri Surakarta II. The method used in this research is descriptive qualitative method. The data in this study is the text of the report on the observation. Sources of data in this study were students of class VII B and C MTs Negeri Surakarta II. The data collection technique used is the classification of the data, then the data is analyzed by distinguishing between denotative and connotative. Based on the results of data analysis known that the data containing denotative and connotative text of the report on the observation of a bouquet of seventh grade students of MTs Negeri Surakarta II is number of 39 data. 20 data that contain denotative and 19 contain connotative meaning of data containing the text of the report the obsevation of a bouquet of seventh grade students of MTs Negeri Surakarta II.